POLITIK KEBUDAYAAN DALAM NOVEL SINDEN KARYA PURWADMADI ADMADIPURWA: KAJIAN SEMIOTIKA ROLAND BARTHES - Nuri Dwi Vindriana; Sunarti Mustamar; Sri Mariati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2018)
This study relies on cultural political issues in the Sinden novel to be analyzed using the concept of Roland Barthes mythology. The mythology looks at the form of speech, including a literary work that reflects and reduces social discourse, cultural, ideological and historical. The method used in this research is a qualitative research method. The analysis has two stages of the sign system. The first system is the sign of denotative sign reading that takes the structural data covering themes, characters, conflicts, and settings that will produce signs. The results mark the first sign of the system as a new marker for a myth reading on both sign system. The reading of the myth in the Sinden novel generates political discourse cultures that reflect events in Indonesia with 1960s background. This study aims to describe the cultural issues covered by political interests and reveal the impact of cultural-political events experienced by the grassroots and increase appreciation of the reader in understanding the Sinden novel.